Response of droplet parameters to liquid viscosity in the flow field of an air-blast sprayer - Zhou, Xi’en; Xiahou, Bing; Zhang, Long; Sun, Daozong; Xue, Xiuyun; Dai, Qiufang; Song, Shuran (International Journal of Agricultural and Biological Engineering, 2023)
The physical properties of sprayed droplets such as viscosity affect their deposition on the target. In order to understand the response characteristics of droplet parameters to the viscosity of a spray solution, a three-dimensional model of the external flow field of an air-blast sprayer based on computational fluid dynamics (CFD) was established according to the actual spray range and the sprayer duct structure. The change rules of droplet diameter and droplet density with distance under different viscosities of the spray solution in the flow field were obtained through numerical solution of the CFD model. The reliability of the model was verified by a chi-squared test comparing the numerical calculations with the results of field experiments. The results showed that the change rule of droplet parameters in an airflow field under different values of the spray solution viscosity was consistent. With the increase in the axial distance, the droplet size decreased initially, then increased, and finally decreased, while the droplet density gradually decreased. Moreover, the greater the spray solution viscosity, the shorter the conveying distance of the droplets in the axial direction, although viscosity was helpful in reducing the droplet drift. In addition, at the same axis distance, with the increased viscosity of the spray solution, the droplet size increased, and the sedimentation of the droplets was more rapid, while the density of the droplets decreased. The results provided a new framework for the study of air-blast spraying technology and serve as a reference for the optimization of the sprayer structure and the preparation method for spray solutions. Keywords: air-blast sprayer, computational fluid dynamics, droplet diameter, droplet density, viscosity DOI: 10.25165/j.ijabe.20231605.7380 Citation: Zhou X E, Xiahou B, Zhang L, Sun D Z, Xue X Y, Dai Q F, et al. Response of droplet parameters to liquid viscosity in the flow field of an air-blast sprayer. Int J Agric & Biol Eng, 2023; 16(5): 28-34